PENGARUH DIGITAL MARKETING, KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI PADA PRODUK KULINER TEGAL DADONG - Handryanus Edwinto Raga; Anak Agung Putu Agung; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
The purpose of this study is to test and obtain empirical evidence of the effect of digital marketing, quality product, and price on purchase intention. The population in this study are people who shop at Kuliner Tegal Dadong. The sample in this study was 80 respondents who were determined based on the non-probability sampling method, namely purposive sampling. The data analysis technique used is multiple linear regression. The results showed that digital marketing, quality product, and price had a positive effect on buying interest.